Measuring Housing Affordability Stress: Can Deprivation Capture Risk Made Real?. Issue 3 (3rd July 2018) - Daniel, Lyrian; Baker, Emma; Lester, Laurence
Abstract: Considerable research effort has sought to understand the prevalence and effects of housing affordability problems in Australian cities and regions. While subject to ongoing debate, the 30/40 ratio indicator of housing affordability stress (HAS) is the most widely used measure. We suggest, however, that it only measures the risk of housing affordability problems. In this paper, we explore material deprivation as a compelling approach to capturing the additional experience and individual impacts of housing affordability problems. We examine the relationship between HAS and material deprivation in a representative sample of household-heads (12, 158) using newly available data from Wave 14 of the HILDA survey. We find that a similar proportion of the population experience HAS or material deprivation, while a smaller number experience both problems in combination. Across these three cohorts, and in comparison with people who experience neither problem, results suggest a gradient pattern for a number of characteristics associated with socio-economic vulnerability. HAS is shown to be an important precondition to material deprivation for many people. We demonstrate the importance of material deprivation within our conceptual understanding of housing affordability problems, finding that it is a necessary addition in order to identify risk made real .